If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 3) + -2x = 4 + 3x Reorder the terms: 2(3 + 4x) + -2x = 4 + 3x (3 * 2 + 4x * 2) + -2x = 4 + 3x (6 + 8x) + -2x = 4 + 3x Combine like terms: 8x + -2x = 6x 6 + 6x = 4 + 3x Solving 6 + 6x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 6x + -3x = 4 + 3x + -3x Combine like terms: 6x + -3x = 3x 6 + 3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 3x = 4 + 0 6 + 3x = 4 Add '-6' to each side of the equation. 6 + -6 + 3x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 4 + -6 3x = 4 + -6 Combine like terms: 4 + -6 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| 5x-4(-1x-3)=8 | | 1.00x+100=2.50x | | 4x+17+4x-39=90 | | 2b+3(b-2)=9 | | 6x-6+3x=-6 | | 8x-4=6x+x+9 | | 3(2x-15)-x=65 | | 1.00x+100=2.50 | | 7x-9-x=3 | | -32-4x=16 | | 7y-7=3+1 | | -8x-6+2x=12-4x | | 2x+5x+20=2x+3 | | 1.00x*100=2.50x | | -3(n-14)=56-n | | 1.00x*100=2.50 | | 2=-14x | | -(6x-5)+4x-6=-1 | | 6x+8x-21=84-7x | | -0.8x-0.6+0.2x=12-4x | | -6x+2-x=2 | | -17-2x=-39 | | 6+x-1+2=7x-5-4x | | -15z=24z+36 | | Fx-gx=z | | 28x+27= | | 2((-8)-2)+8= | | 3x(2x+20)=4x-20 | | -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x |